World-Class Universities and the Common Good - Tian, Lin; Yan, Wu; Liu, Nian Cai (International Higher Education, 2018)
Based on UNESCO’s report Rethinking Education towards a Global Common Good (2015) and developments in higher education, this article explores the reasons behind the shift from “public good” to “common good” in higher education. It focuses on the special role of world-class universities (WCUs) with regard to the global common good, as a result of their international orientation and emphasis on global development and the well-being of global communities. WCUs deliver advanced knowledge and research outputs and, more importantly, help shape and realize the global common good (i.e., the promotion of peace) shared by all mankind.